Síntese e caracterização de catalisadores à base de alumina, impregnada com cálcio e níquel, para reforma do gás natural - Silva, José Francisco Lima (2015)
The replacement of fossil fuels with energy sources that are renewable and non-polluting has contributed to the technological growth. An example of this is the growing interest in the use of hydrogen as fuel. Natural gas is an important function in the supply of fuel demand in the coming years; it appears as a good alternative source of hydrogen. Its consumption is less than production capacity and, thus, new technologies have been developed in order to transform natural gas into higher value-added products. The dry reforming of natural gas is the main route to produce H2 or synthesis gas (CO + H2). This study aims to investigate the effect of adding calcium oxide (CaO) in the nickel catalyst composition supported on γ-Al2O3 in the catalyst performance across the methane dry reforming reaction. The catalytic support was prepared by the replica method, using polyurethane foam as a template, followed by wet impregnation of calcium (Ca) and nickel (Ni). The catalysts were characterized by, thermogravimetric analysis (TGA), atomic absorption spectroscopy (AAS), diffraction X-ray (XRD) analysis, fluorescence X-ray (XRF), temperature programmed reduction (TPR) through physical adsorption nitrogen (BET method), scanning electron microscopy (SEM) and temperature programmed desorption (TPD-CO2). The catalytic tests were carried out in the gas phase under atmospheric pressure using a fixed bed reactor by varying the reaction temperature of 550ºC, 650ºC and 750ºC and a molar ratio of reactants of 1:1 (CH4 : CO2). N2 was employed as diluent gas as well as internal standard for gas chromatographic analysis. The catalyst was activated at 850°C under H2 flow for 30 min. For the analysis of the reaction products using a gas chromatograph was equipped with a packed column (Molecular sieve 5A and Porapak Q) and thermal conductivity detector. The addition of calcium led to increased conversion of methane with lower coking.